2013
DOI: 10.1007/s40273-013-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Rivaroxaban Versus Warfarin for Stroke Prevention in Atrial Fibrillation in the Belgian Healthcare Setting

Abstract: BackgroundWarfarin, an inexpensive drug that has been available for over half a century, has been the mainstay of anticoagulant therapy for stroke prevention in patients with atrial fibrillation (AF). Recently, rivaroxaban, a novel oral anticoagulant (NOAC) which offers some distinct advantages over warfarin, the standard of care in a world without NOACs, has been introduced and is now recommended by international guidelines.ObjectiveThe aim of this study was to evaluate, from a Belgian healthcare payer perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…Although there were substantial differences in the model structure and usage of utilities, their results are similar to those of our analysis (ICER ranging from dominance to €20,089 per QALY) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although there were substantial differences in the model structure and usage of utilities, their results are similar to those of our analysis (ICER ranging from dominance to €20,089 per QALY) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…Whereas European studies yielded an incremental cost-effectiveness ratio (ICER) ranging from dominance to €20,089 per quality-adjusted life-year (QALY) [16][17][18][19][20], the ICERs of studies conducted in the US or Canada ranged from $3,200 to $55,800 per QALY [21][22][23]. However, to date, no study has evaluated the cost effectiveness of rivaroxaban compared with conventional warfarin for the German healthcare system.…”
mentioning
confidence: 99%
“…This avoids the situation of an intervention being compared with a treatment option that is not cost effective and, thereby, misguiding healthcare providers to make non-efficient decisions of limited resources. Whilst all four NOACs were found to be cost effective in comparison to warfarin (consistent with earlier findings [20,24]), the incremental analysis highlighted that dabigatran 150 mg dominated dabigatran 110 mg and apixaban extendedly dominated both dabigatran 150 mg and rivaroxaban, although differences are small. Thus, the deterministic analysis would suggest that from available OACs on the Belgian market, apixaban and warfarin represent the ''best that the system can do with available agents at current prices'' [25].…”
Section: Discussionsupporting
confidence: 82%
“…Amongst those, two studies have compared an individual NOAC with VKA treatment from a Belgian perspective [20,24]. Simultaneous assessment of the efficiency of the new interventions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Beckman et al, PE monotherapy with enoxaparine was shown to cause a 2-day decrease in the median LOS compared with the standard regimen (10). In a study in which Markov modeling was constructed based on the EINSTEIN-PE study, Lefebvre et al (11) showed that rivaroxaban therapy costs $2.448 per Even though there has been no published study about the diagnosis and treatment costs of PE in our country, studies comparing these three pharmaceuticals for deep-vein thrombosis, PE, stroke, nonvalvular atrial fibrillation treatment, and orthopedic postoperative prophylaxis demonstrated that new oral anticoagulants were more costeffective than warfarin and enoxaparine (11)(12)(13)(14)(15)(16). However, it should be remembered that costs related to hospitalization and complications are also included in these studies.…”
Section: Discussionmentioning
confidence: 99%